2008
DOI: 10.1007/s10336-008-0333-7
|View full text |Cite
|
Sign up to set email alerts
|

Variation in home-range size and movements of wintering dabbling ducks

Abstract: International audienceDespite a long historical record of radio-tracking analyses, basic home-range information is still lacking for most common waterfowl species, especially during the winter. We investigated how dabbling duck home ranges and daily foraging movements are influenced by extrinsic (site, temperature, date) and intrinsic factors (species, sex, age). We radio-tagged and monitored 125 individuals of three duck species (mallard Anas platyrhynchos, Eurasian teal A. crecca crecca and northern pintail … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
44
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 54 publications
7
44
1
Order By: Relevance
“…This corroborates earlier studies relying on radio-tracking techniques, suggesting that ducks repeatedly come back to the same roost day after day (e.g. Tamisier & Tamisier 1981, Cox & Afton 1996, Guillemain et al 2002, Legagneux et al 2009a). Another conclusion from our study is that teal are unlikely to simply have moved to surrounding marshes when they are not detected at their traditional day roost, but should rather be considered as having left the wintering quarter overall, or being dead.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This corroborates earlier studies relying on radio-tracking techniques, suggesting that ducks repeatedly come back to the same roost day after day (e.g. Tamisier & Tamisier 1981, Cox & Afton 1996, Guillemain et al 2002, Legagneux et al 2009a). Another conclusion from our study is that teal are unlikely to simply have moved to surrounding marshes when they are not detected at their traditional day roost, but should rather be considered as having left the wintering quarter overall, or being dead.…”
Section: Discussionsupporting
confidence: 80%
“…To our knowledge, the fact that wintering dabbling ducks distribute themselves and partition their activities in general accordance with the functional unit principle has always been supported by studies dealing with wintering duck habitat selection (e.g. Tamisier & Tamisier 1981, Cox & Afton 1996, Duncan et al 1999, Guillemain et al 2002, Legagneux et al 2009a. However, other studies also suggest that, despite following this general pattern, some individuals may nonetheless move within their winter quarter and therefore switch between day roosts separated by distances of several kilometres (Guillemain et al 2002, Legagneux et al 2009b.…”
mentioning
confidence: 90%
“…One of 21 individuals was found dead three days after logger deployment, but this was likely unrelated to tag attachment. Similarly, radio transmitters were glued and bound to the tail feathers of Mallard, Eurasian Teal and Northern Pintail in France by Legagneux et al [50], but no details are provided about whether or not this affected the birds. Seven out of 20 tail-mounted transmitters of 17 g in Barnacle Geese were lost prematurely in a study by Phillips et al [64], but no transmitter effects on the birds were reported.…”
Section: Other Attachment Methodsmentioning
confidence: 99%
“…A total of 2,144 locations in spring and 1,952 locations in winter were collected for space analysis in our study. Before analyzing the home range, data area curves were used to determine the minimum number of locations needed for per individual (Legagneux et al 2009). We tested for the effect of the number of locations on estimated size as the criterion that increased each 10 locations less than 10% increase in home range size (Odum and Kuenzler 1955).…”
Section: Study Areamentioning
confidence: 99%